Limitations of the Use of Pressure Waves to Verify Correct Epidural Needle Position in Dogs - Chiara Adami; Alessandra Bergadano; Claudia Spadavecchia (Veterinary Medicine International)
The use of pressure waves to confirm the correct position of the epidural needle has been described in several domestic species and proposed as a valid alternative to standard methods, namely, control radiographic exam and fluoroscopy. The object of this retrospective clinical study was to evaluate the sensitivity of the epidural pressure waves as a test to verify the correct needle placement in the epidural space in dogs, in order to determine whether this technique could be useful not only in the clinical setting but also when certain knowledge of needle’s tip position is required, for instance when performing clinical research focusing on epidural anaesthesia. Of the 54 client-owned dogs undergoing elective surgeries and enrolled in this retrospective study, only 45% showed epidural pressure waves before and after epidural injection. Twenty-six percent of the animals showed epidural pressure waves only after the injection, whereas 29% of the dogs showed epidural pressure waves neither before nor after injection and were defined as false negatives. Our results show that the epidural pressure wave technique to verify epidural needle position lacks sensitivity, resulting in many false negatives. As a consequence, the applicability of this technique is limited to situations in which precise, exact knowledge of the needle's tip position is not mandatory.